Design, synthesis and anti-inflammatory activity of imidazol-5-yl pyridine derivatives as p38 alpha/MAPK14 inhibitor - Ali, Eslam M. H.; Abdel-Maksoud, Mohammed S.; Hassan, Rasha Mohamed; Mersal, Karim I.; Ammar, Usama M.; Se-In, Choi; He-Soo, Han; Kim, Hee-Kwon; Lee, Anna; Lee, Kyung-Tae; Oh, Chang-Hyun (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
P38 alpha VMAPK14 is intracellular signalling regulator involved in biosynthesis of inflammatory mediator cytokines (TNF-alpha, IL-1, IL-6, and IL-1b), which induce the production of inflammatory proteins (iNOS, NF-kappa B, and COX-2). In this study, drug repurposing strategies were followed to repositioning of a series of B-RAF(V600E) imidazol-5-yl pyridine inhibitors to inhibit P38a kinase. A group 25 reported P38a kinase inhibitors were used to build a pharmacophore model for mapping the target compounds and proving their affinity for binding in P38a active site. Target compounds were evaluated for their potency against P38a kinase, compounds 1 la and 11d were the most potent inhibitors (IC50 = 47 nM and 45 nM, respectively). In addition, compound 11d effectively inhibited the production of pminflammatory cytokines TNF-alpha, 1L-6, and 1L-1 beta in LPS-induced RAW 264.7 macrophages with IC50 values of 78.03 mu M, 17.6 nM and 82.15 nM, respectively. The target compounds were tested for their anti-inflammatory activity by detecting the reduction of Nitric oxide (NO) and prostaglandin (PGE2) production in LPS-stimulated RAW 264.7 macrophages. Compound 11d exhibited satisfied inhibitory activity of the production of PGE2 and NO with IC(50 )values of 0.29 mu M and 0.61 mu M, respectively. Molecular dynamics simulations of the most potent inhibitor 11d were carried out to illustrate its conformational stability in the binding site of P38a kinase.